Pemberian Range of Motion Aktif Ektremitas Bawah Pada Penderita Ulkus Diabetikum Dengan Gangguan Mobilitas Fisik - Wulan Candeli; Sudiarto S; Fida Dyah Puspasari (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Background : Range Of Motion (ROM) is an exercise performed to improve the ability to maintain or improve normal and complete joint movement and increase muscle mass and tone. Diabetes is a chronic diasease that can occur when the pancrease is no longer able to produce insulin. Therefore, the main factor in this case is usually diabetic foot ulcels in diabetics. Purpose: To describe the nursing care of diabetic ulcer patients on the use of active ROM. Reseacrh Method : case study. Results: During 3 consecutive days of nursing care using ROM in diabetic ulcer patiens, the value of muscle strength in the left lower extremity was 2 witch change to 4. Conclusion: Active Range Of Motion (ROM) exercises can increase mobilization in diabetic ulcer patients. By doing this ROM exercise, it can be an alternative to increase the range of motion in diabetic ulcer patients.